PENGEMBANGAN MODUL SISTEM PENCERNAAN BERBASIS INKUIRI TERINTEGRASI SAINS-ISLAM UNTUK MENINGKATKAN RELIGIUSITAS SISWA - Nila Masnuri Yunita; Maridi Maridi; Baskoro Adi Prayitno (P-2623-0291)
This study aims to: (1) Develop an integrated Inquiry-based Biology module integrated with Islamic Science to improve the religious behavior of grade XI high school students. (2) Knowing the feasibility of the Science-based Biology Inquiry module in Islamic-based Schools. This type of research is research and development by using a modification of the Four-D Model (4-D Model) which consists of 4 stages, namely: defining, designing, developing, and distributing (developing) disseminate). Qualitative data were obtained from observations and questionnaires, while quantitative data were obtained from the results of the module validation, questionnaire assessments in product trials (limited trials and extensive trials), operational trials and questionnaires on Islamic knowledge of Islamic cuisine. The results of this study indicate that: (1) the validation of Biology and Qur'an material experts and Hadith are in very reasonable criteria (88.5%); (2) media validation in the criteria is very feasible (90%); (3) language validation in the criteria is very feasible (93.75%); (4) learning device validation (95.31%). The results of the assessment of education practitioners are 88.01 and colleagues 90.71, which means the module is very feasible to use. In conclusion, Digestion System Module based on Inquiry integrated  Islamic Science for Class XI High School is proper to be used as a support for the learning of the Digestive System in an Islamic-based school environment